The Position Of Women Sentana Peperasan (Appropriate Children) View From The Perspective Of Bali Traditional Health Law - I Putu Windu Mertha Sujana; I Wayan Landrawan; Ni Made Widya Sari (Dwijendra University, 2022)
The presence of children in a family is the most coveted thing by every married couple. Various efforts can be made by humans to obtain children, one of which is by adopting children. One of the goals of adopting a child is none other than as a successor to the offspring and heirs of his adoptive parents. In Bali, the adoption of a child has a separate legal relationship between the child and his adoptive parents. Through the Dewa Saksi ceremony, religiously the child will become the biological child of his adoptive parents. In addition, even though Bali adheres to a patrilineal system, adopted daughters have the opportunity to being the main heirs in their adoptive families, namely by being made sentana rajeg. Sentana rajeg is a condition in which the daughters are given the status of sons (purusa) in Nyeburin marriages in Bali. Thus, the adopted daughter can be domiciled as the main heir in the adoptive family. To find a solution to these problems, therefore an analysis is needed regarding the position of adopted daughters in Balinese customary inheritance law. The method used to compile this article is literature study or literature study. The result of this research was through the decision of Pasamuhan Agung III/2010, the position of the woman can be one of the heirs and get a certain portion of the inheritance without having to be made a sentana rajeg first.